Strategies Of Elementary School Teachers To Teach Practicum-Based Science In The Midst Of Limited Laboratory Facilities - rusdi, indah sari (SEARCH: Science Education Research Journal, 2024)
This study aims to understand the Strategy of Elementary School Teachers in Teaching Practicum-Based Science in the Middle of Laboratory Facility Limitations. Papua has several important characteristics. Teachers seek to integrate students' local experiences and knowledge in Papua into science learning, encourage students to make observations and hands-on practice in the surrounding environment, and discuss the application of science concepts to preserve nature. Although the majority of primary schools in Papua do not have adequate laboratories, teachers make creative efforts to ensure that the science learning process runs effectively, such as using direct demonstration methods in the classroom by utilizing simple materials and inviting students to conduct simple experiments in the environment around the school. Overall, the results of this study show that the teachers at SD Inpress 56 are trying to optimize science learning by utilizing available resources, and teachers' creativity and innovation are the key in creating interesting and meaningful science learning for students. This study uses a qualitative research method with a descriptive approach, which aims to describe phenomena related to forms, activities, characteristics, changes, relationships, similarities, and differences. The data analysis process is carried out through 4 stages, namely data collection, data reduction, data presentation, and drawing conclusions. The research subjects consisted of 3 teachers at the school.